Efeitos da nanopartícula de ácido poli lático-co-glicólico (PLGA) associada ao cloridrato de metformina na doença periodontal em ratos diabéticos - Pereira, Aline de Sousa Barbosa Freitas (2022)
There is an association between diabetes and periodontitis, and Metformin (MET) in addition to controlling glycemic levels, has shown anti-inflammatory effects and decreased periodontal bone loss. By transferring MET to a nanoparticle system, the advantage of increasing therapeutic efficacy can be presented. Objectives: this study consisted of evaluating the anti-inflammatory effects, bone loss and in vitro/in vivo availability of a polylactic-co-glycolic acid (PLGA) nanoparticle associated with MET in a ligature-induced periodontitis model. Materials and methods: PLGA loaded with different doses of MET was characterized by its mean diameter, particle size, polydispension index and entrapment efficiency. Male Wistar rats were used, randomly divided into control and experimental groups with different doses of MET associated or not with PLGA, which received different treatments. Samples of jaws and gingival tissues were used to assess bone loss and inflammation, using computed microtomography, histopathology, immunohistochemistry, analysis of inflammatory cytokines and gene expression of proteins by quantitative RT-PCR. For the in vitro release assay, the static Franz vertical diffusion cell device was used. For in vivo availability, blood samples were collected at different time intervals and analyzed by high performance liquid chromatography coupled with mass spectrometry (HPLC-MS/MS). Results: the mean diameter of MET-loaded PLGA nanoparticles was in the range of 457.1 ± 48.9 nm (p <0.05) with a polydispersity index of 0.285 (p <0.05), Z potential of 8.16 ± 1.1 mV (p <0.01) and trapping efficiency (EE) of 66.7 ± 3.73. Treatment with MET 10 mg/kg + PLGA showed a low concentration of inflammatory cells, weak immunostaining for RANKL, Cathepsin K, OPG and osteocalcin. Decreased IL-1β and TNF-α levels (p <0.05), increased AMPK gene expression (p <0.05) and decreased NF-κB p65, HMGB1 and TAK-1 (p <0. 05). The 10 mg/kg MET + PLGA was released in the in vitro assay suggesting a kinetic model of parabolic diffusion with a release profile that reaches 50% of its content in 2h and remains in constant release around 60% until the end of 6h . The in vivo assay showed the apparent volume of distribution Vz/F (10 mg/kg MET + PLGA, 46.31 mL/kg vs. 100 mg/kg MET + PLGA, 28.8 mL/kg) and the mean MRTinf residency (PLGA + MET 10 mg/kg, 37.66h vs. MET 100 mg/kg, 3.34h). Conclusion: MET-loaded PLGA decreased inflammation and bone loss in periodontitis in diabetic rats. 10 mg/kg MET + PLGA had a slower rate of elimination compared to 100 mg/kg MET. The formulation modifies pharmacokinetic parameters such as apparent volume of distribution and mean residence time.